PENGARUH BERBAGAI JENIS BOKASHI TERHADAP SERAPAN FOSFOR TANAMAN JAGUNG MANIS (Zea mays saccarata) - Morgo,Abdul Rahim Thaha, Yosep S Patadungan, Safitra (AGROTEKBIS, 2015)
The aim of this research is to determine the effect of various types of bokashi on phosphorus uptake of sweet corn crops. The research was conducted in the village of Sidera, District Biromaru, Sigi, Central Sulawesi Province. Analysis of soil, plant tissue and bokashi performed in the Laboratory of Soil Science, Faculty of Agriculture, University of Tadulako, Palu. This research was arranged in Randomized Block Design (RBD), which consists of 7 treatments and replicated 3 times so that there are 21 experimental units. Treatment that consists of control and 6 types of biomass materials of gamal, venus, peanuts, chicken manure, goat manure and cow dung, each is used as much as 15 t ha-1. The results showed that application of various types of bokashi with a dose of 15 t ha-1 increased C-organic of soil, soil pH, total P, available P and phosphorus uptake of plant sweet corn. HSD test results (5%) indicate that P uptake is highest in bokashi treatment gamal (6,74g/plant) were significantly different with bokashi treatment peanuts (3,34 g/plant), bokashi venus (3,05 g/plant), bokashi goat manure (3.01 g/plant), bokashi cow manure (1.62 g/plant), bokashi chicken manure (0,96 g/plant), and control (0,28 g/plant). In the treatment of peanut bokashi no real difference in bokashi venus and goat manure but all three types are significantly different bokashi cow manure, chicken manure and control.